2015
DOI: 10.1128/iai.00081-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of OprF as a Complement Component C3 Binding Acceptor Molecule on the Surface of Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a versatile opportunistic pathogen that can cause devastating persistent infections. Complement is a highly conserved pathway of the innate immune system, and its role in the first line of defense against pathogens is widely appreciated. One of the earliest events in the complement cascade is the conversion of C3 to C3a and C3b, the latter typically binds to one or more acceptor molecules on the pathogen surface. We previously demonstrated that complement C3b binding acceptors exist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…The antimicrobial activity of these serum proteins is enhanced in the acidic and hypocalcemic conditions characteristic of infected and inflamed tissue [64]. The P. aeruginosa outer membrane porin OprF serves as a binding acceptor molecule for C3b to initiate formation of the membrane attack complex (MAC) [65], but another bacterial protein, dihydrolipoamide dehydrogenase (Lpd), can inhibit MAC deposition and limit complement damage [66]. Of interest, P. aeruginosa can stimulate neutrophils to undergo neutrophil extracellular trap (NET) formation with activation and deposition of the C5b-9 MAC on NETs, potentially contributing to local host cell damage and death [67].…”
Section: Immune Recognition and Response To P Aeruginosa Infectionmentioning
confidence: 99%
“…The antimicrobial activity of these serum proteins is enhanced in the acidic and hypocalcemic conditions characteristic of infected and inflamed tissue [64]. The P. aeruginosa outer membrane porin OprF serves as a binding acceptor molecule for C3b to initiate formation of the membrane attack complex (MAC) [65], but another bacterial protein, dihydrolipoamide dehydrogenase (Lpd), can inhibit MAC deposition and limit complement damage [66]. Of interest, P. aeruginosa can stimulate neutrophils to undergo neutrophil extracellular trap (NET) formation with activation and deposition of the C5b-9 MAC on NETs, potentially contributing to local host cell damage and death [67].…”
Section: Immune Recognition and Response To P Aeruginosa Infectionmentioning
confidence: 99%
“…Since bacterial outer membrane proteins (OMPs) play a crucial role in interaction of pathogens with immune cells (Confer and Ayalew, 2013), we determined the role of P. aeruginosa OprF in bacterial survival inside macrophages. OprF is the major OMP of P. aeruginosa and has been demonstrated to play an important role in interaction of this pathogen with host cells (Nestorovich et al, 2006; Bouffartigues et al, 2012; Reusch, 2012; Mishra et al, 2015). We observed that survival of otopathogenic P. aeruginosa inside macrophages requires bacterial oprF expression.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand blot experiments described here failed to detect binding of C3 to OprF, as described Mishra et al . (). It is possible that the human serum used by these researchers contained specific antibodies against OprF.…”
Section: Discussionmentioning
confidence: 97%
“…Mishra et al . used 20% normal human serum (Mishra et al ., ), while we used 2 μg/ml of C3 or 0.2% normal human serum. Indeed, in preliminary experiments using 20 μg/ml C3 or 20% normal human serum, we were able to detect OprF as a C3 binding molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation